Business Policy and Metaphysics: Some Philosophical Considerations - Mitroff, Ian I.; Mason, Richard O. (Academy of Management Review, 1982)
Business policy is described as an exercise in applied metaphysics. Policy making requires the manager to go beyond knowledge derived purely from direct experience, to deal with questions concerning the nature and structure of reality, and to create methods for acquiring knowledge about the world in which his enterprise operates. Twelve approaches that typify the field of business policy are summarized and classified as to their primary metaphysical assumptions, using two key dimensions, rationalism versus existentialism and empiricism versus idealism.